2009
DOI: 10.3348/jksr.2009.60.5.325
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence at the Bronchial Stump Site of Post-Operative Non-Small Cell Lung Cancer Patients: Comparison of CT Findings and Bronchoscopy

Abstract: Purpose:To compare computed tomography (CT) images and bronchoscopic findings of local tumor recurrence at the bronchial stump site in post-operative non-small cell lung cancer (NSCLC) patients. Materials and Methods: A retrospective study was conducted to review the CT images of 9 lung cancer cases that recurred at the bronchial stump site on 576 resected primary non-small cell lung cancers over a 9-year period. The CT images of the bronchial stump site recurrence were classified as: bronchial wall thickening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…The exclusion of these cases, and also, the exclusion of patients with mediastinal lymph node metastasis could be the reasons for our lower BSR rate. However, as has been shown in previous studies, 5,10,11,13 our study confirmed that, although a thorough microscopic evaluation showed that the resection margin was clear after lung cancer surgery, BSR can develop. Regarding BSR after complete resection, it is possible that the bronchial margin showed no evidence of disease after conventional histopathologic examination can have overlooked cancer cells; microscopic evaluation may not be sufficient to confirm the absence of residual cancer cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The exclusion of these cases, and also, the exclusion of patients with mediastinal lymph node metastasis could be the reasons for our lower BSR rate. However, as has been shown in previous studies, 5,10,11,13 our study confirmed that, although a thorough microscopic evaluation showed that the resection margin was clear after lung cancer surgery, BSR can develop. Regarding BSR after complete resection, it is possible that the bronchial margin showed no evidence of disease after conventional histopathologic examination can have overlooked cancer cells; microscopic evaluation may not be sufficient to confirm the absence of residual cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…In those articles, it was reported that 2.1 to 3.4% of the patients develop BSR after surgical treatment. 5,[10][11][12] In some studies, only patients with complete resection were included 10,11 ; however, most of the studies also had patients with microscopically incomplete cancer resections, and all the studies had patients with mediastinal lymph node metastasis. No study has compared patients with and without BSR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation